Hollow glass bead as well as preparation method and application thereof

By adjusting the composition ratio and preparation method of hollow glass microbeads, the problem of poor insulation and thermal insulation effect of existing hollow glass microbeads is solved, and significant heat reduction and energy consumption reduction are achieved, and the thermal insulation and waterproofing of the paint are enhanced. Anti-fouling and corrosion resistance.

CN119161098APending Publication Date: 2024-12-20QINHUANGDAO GLASS IND RES & DESIGN INST +1

Patent Information

Application Number
CN202411233962.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing hollow glass microbeads have poor thermal insulation effects in the construction field, making it difficult to effectively reduce the heat accumulation and energy consumption of buildings.

Method used

By adjusting the composition ratio of hollow glass microbeads, including silica, boron oxide, sodium oxide, cuprous oxide, barium oxide, chromium oxide, nickel oxide, tin oxide and silicon carbide, and using specific preparation methods, the formation of Microbeads with excellent thermal insulation properties.

Benefits of technology

It significantly reduces the heat conduction and thermal radiation of the building, improves the thermal insulation performance of the coating, reduces energy consumption, and enhances the waterproof, anti-fouling and corrosion resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005027165420000111
    Figure BDA0005027165420000111
  • Figure BDA0005027165420000121
    Figure BDA0005027165420000121
  • Figure BDA0005027165420000122
    Figure BDA0005027165420000122
Patent Text Reader

Abstract

The invention relates to the technical field of thermal insulation materials, and discloses a hollow glass bead as well as a preparation method and application thereof. The hollow glass beads are prepared from the following components in percentage by weight: 40 to 65 percent of silicon dioxide, 5 to 15 percent of boron oxide, 5 to 15 percent of sodium oxide, 2 to 8 percent of cuprous oxide, 1 to 5 percent of barium oxide, 2 to 10 percent of chromic oxide, 3.5 to 7.5 percent of nickel oxide, 1.5 to 3 percent of tin oxide and 1 to 5.5 percent of silicon carbide. Cuprous oxide, barium oxide and chromic oxide have high reflection coefficients, and heat absorption of buildings can be reduced; nickel oxide, tin oxide and silicon carbide have high radiation coefficients, heat can be dissipated into outdoor air in an infrared radiation mode, and therefore the temperature of the outer surface of a building is reduced. Cuprous oxide can significantly improve the surface cleanliness of the coating and enhance the thermal insulation performance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat insulation materials, and in particular to hollow glass microspheres and a preparation method and application thereof. Background Art

[0002] The construction sector is considered to be one of the main areas of energy consumption, and the energy consumed by global buildings accounts for about 40% of the total energy consumption. In the building structure, the heat dissipated by the wall accounts for about 20% of the total heat dissipation in the building sector, and the heat absorbed by the exterior wall in summer is about 30% of the total heat absorbed by the building. Therefore, building thermal insulation is one of the important measures to reduce energy consumption. As a new type of coating, thermal insulation coating can play a role in heat insulation when applied to the construction surface. It has the characteristics of low energy consumption and low pollution. It is the most effective and convenient energy-saving measure so far. It can significantly reduce the heat accumulation of buildings, improve the living and working environment, and play an important role in energy conservation and emission reduction.

[0003] Hollow glass microspheres are tiny, hollow spherical powders with the characteristics of light weight, large volume, high compressive strength, good dispersibility, fluidity and stability. Existing hollow glass microspheres are composed of silicon dioxide, boron oxide, sodium oxide, titanium dioxide, aluminum oxide, calcium oxide and copper oxide. Although they have good adhesion and chemical stability and are widely used in coatings, their thermal insulation effect is poor.

[0004] Therefore, how to obtain a hollow glass microsphere with heat insulation effect is one of the technical problems that need to be solved urgently in this field. Summary of the invention

[0005] In view of this, the present invention provides a hollow glass microsphere with heat insulation effect.

[0006] The invention also provides a method for preparing the hollow glass microspheres.

[0007] In a first aspect, the present invention provides a hollow glass microsphere, which comprises the following components: 40wt%-65wt% of silicon dioxide, 5wt%-15wt% of boron oxide, 5wt%-15wt% of sodium oxide, 2wt%-8wt% of cuprous oxide, 1wt%-5wt% of barium oxide, 2wt%-10wt% of chromium oxide, 3.5wt%-7.5wt% of nickel oxide, 1.5wt%-3wt% of tin oxide, and 1wt%-5.5wt% of silicon carbide.

[0008] In an optional embodiment, the hollow glass microspheres include the following components: 45wt%-60wt% of silicon dioxide, 10wt%-15wt% of boron oxide, 8wt%-12wt% of sodium oxide, 5wt%-8wt% of cuprous oxide, 2wt%-3.5wt% of barium oxide, 3wt%-8wt% of chromium oxide, 3.5wt%-7wt% of nickel oxide, 1.5wt%-2.5wt% of tin oxide, and 2wt%-5wt% of silicon carbide.

[0009] In an optional embodiment, the hollow glass microspheres include the following components: 50wt%-55wt% silicon dioxide, 10wt%-12wt% boron oxide, 10wt%-12wt% sodium oxide, 5wt%-7wt% cuprous oxide, 2wt%-3.5wt% barium oxide, 6wt%-6.5wt% chromium oxide, 4wt%-6wt% nickel oxide, 1.5wt%-2wt% tin oxide, and 2wt%-3.5wt% silicon carbide.

[0010] In an optional embodiment, the particle size of the hollow glass microspheres is 10 μm-50 μm.

[0011] In a second aspect, the present invention also provides a method for preparing hollow glass microspheres, comprising the following steps:

[0012] (1) weighing quartz sand, boric acid, soda ash, cuprous oxide, barium sulfate, chromium oxide, nickel oxide, tin oxide, and a foaming agent, mixing and heating once to obtain a molten glass liquid; rapidly cooling the molten glass liquid, grinding, and obtaining a glass powder containing gas therein;

[0013] (2) The glass powder is heated for a second time at 400° C.-800° C. to obtain the obtained product.

[0014] In an optional embodiment, the mass ratio of the quartz sand, the boric acid, the soda ash, the cuprous oxide, the barium sulfate, the chromium oxide, the nickel oxide, the tin oxide, the silicon carbide, and the foaming agent is 40-65: 8.88-26.64: 8.55-25.65: 2-8: 1.52-7.61: 2-10: 3.5-7.5: 1.5-3: 1-5.5: 4-8.

[0015] In an optional embodiment, the foaming agent includes at least one of carbon powder, carbonate, sulfate, nitrate, and manganese dioxide.

[0016] In an optional embodiment, the carbonate includes at least one of sodium carbonate, calcium carbonate, and magnesium carbonate.

[0017] In an optional embodiment, the sulfate includes at least one of sodium sulfate and calcium sulfate.

[0018] In an optional embodiment, the nitrate includes at least one of lithium nitrate, sodium nitrate and potassium nitrate.

[0019] In an optional embodiment, the primary heating temperature is 1100° C.-1250° C., and the heating time is 20 min-60 min.

[0020] In an optional embodiment, the secondary heating time is 10 min-30 min.

[0021] In a third aspect, the present invention further provides a thermal insulation coating, comprising hollow glass microspheres and water-based coating, wherein the hollow glass microspheres are the above-mentioned hollow glass microspheres.

[0022] In an optional embodiment, the mass of the hollow glass microspheres accounts for 5wt%-40wt% of the thermal insulation coating.

[0023] In an optional embodiment, the water-based coating includes at least one of water-based polyurethane, water-based polyacrylic resin, and water-based silicone-acrylic coating.

[0024] In a fourth aspect, the present invention also provides an application of the above-mentioned thermal insulation coating in the field of construction.

[0025] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0026] 1. The hollow glass microspheres provided by the present invention include the following components: 40wt%-65wt% of silicon dioxide, 5wt%-15wt% of boron oxide, 5wt%-15wt% of sodium oxide, 2wt%-8wt% of cuprous oxide, 1wt%-5wt% of barium oxide, 2wt%-10wt% of chromium oxide, 3.5wt%-7.5wt% of nickel oxide, 1.5wt%-3wt% of tin oxide, and 1wt%-5.5wt% of silicon carbide. As the main component of glass, silicon dioxide is the skeleton of glass, which can increase the viscosity of glass liquid and improve the mechanical strength of glass. The present invention limits the silicon dioxide content to 40wt%-65wt%, which can reduce the melting temperature of glass liquid while meeting the strength of hollow glass microspheres, reduce energy consumption in the preparation process, and reduce production costs; boron oxide can improve the physical and chemical properties of glass, improve the transparency, heat resistance and corrosion resistance of glass, and can also reduce the melting point and viscosity of glass, promote the fluidity and formability of glass. Too low a content will increase the melting temperature of glass liquid and reduce transparency. Too much content will make the glass network structure loose, increase the thermal expansion coefficient of glass, and work together with barium oxide to affect the refractive index effect of hollow glass microspheres; sodium oxide has a low melting point and good melting performance, can greatly reduce the viscosity of glass liquid, is a flux for manufacturing glass, can reduce the melting temperature of glass, accelerate the melting speed, and promote the formation of glass. Too much sodium chloride content will greatly reduce the chemical stability, thermal stability and mechanical strength of the glass, and easily cause the glass to mold and increase the production cost of the glass; cuprous oxide can enhance the hardness and wear resistance of hollow glass microspheres, and also has an anti-corrosion effect. Coating it on metal materials can significantly slow down rust; barium and other metals exist in the form of oxides. Barium oxide can not only reduce the melting temperature of glass, but also has a high refractive index, which can significantly enhance the heat insulation and cooling performance of the coating; tin oxide has good heat insulation performance and hardness, can significantly enhance the heat insulation performance of the coating, and improve the wear resistance and corrosion resistance of the coating; cuprous oxide, barium oxide, chromium oxide, nickel oxide, tin oxide, and silicon carbide are functional components of hollow glass microspheres. Too high or too low a content will significantly reduce the emissivity and refractive index of the hollow glass microspheres. The present invention limits their contents respectively, which can significantly improve the emissivity and refractive index of the hollow glass microspheres and greatly enhance the heat insulation and thermal insulation performance of the coating.

[0027] When doors and windows are closed, heat is mainly transferred to the room through heat conduction and heat radiation. Cuprous oxide, barium oxide, and chromium oxide have high reflectivity, which can reduce the building's absorption of heat. Nickel oxide, tin oxide, and silicon carbide have high emissivity, which can dissipate heat into the outdoor air in the form of infrared radiation, thereby reducing the temperature of the building's outer surface. In addition, cuprous oxide has an antibacterial effect, which can significantly improve the cleanliness of the coating surface and enhance the coating's thermal insulation performance.

[0028] The hollow glass microspheres contain gas, which can not only improve the elasticity of the coating and prevent the coating from cracking and falling off due to thermal expansion and contraction; it can also enhance the waterproof, anti-fouling, and anti-corrosion properties of the coating, and reduce the unit volume cost of the coating; in addition, the spherical surface of the hollow glass microspheres has a reflective effect on light, and the air contained in the tightly arranged hollow glass microspheres can reduce the thermal conductivity of the coating, further improving the thermal insulation performance of the coating.

[0029] 2. The preparation method of hollow glass microspheres provided by the present invention limits the secondary heating temperature to 400°C-800°C, so that the glass particles containing air inside slowly form a hollow structure, and the obtained hollow glass microspheres have uniform thickness and a high yield rate; if the temperature is too high, the glass microspheres are likely to break, and the yield rate is low.

[0030] 3. The thermal insulation coating provided by the present invention can be applied on the surface of window glass to significantly reduce its thermal conductivity (the thermal conductivity of existing coatings is 0.06-0.2W / (m·K)), and the thermal conductivity is as low as 0.03-0.07W / (m·K), thereby reducing the entry of outdoor heat in summer and the loss of indoor heat in winter, thereby reducing energy consumption. DETAILED DESCRIPTION

[0031] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0032] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0033] In order to solve the problems existing in the above-mentioned related art, according to the first aspect of the present invention, the present invention provides a hollow glass microsphere, wherein the hollow glass microsphere comprises the following components: 40wt%-65wt% of silicon dioxide, 5wt%-15wt% of boron oxide, 5wt%-15wt% of sodium oxide, 2wt%-8wt% of cuprous oxide, 1wt%-5wt% of barium oxide, 2wt%-10wt% of chromium oxide, 3.5wt%-7.5wt% of nickel oxide, 1.5wt%-3wt% of tin oxide, and 1wt%-5.5wt% of silicon carbide; preferably, 45wt%-60wt% of silicon dioxide, 10wt%-15wt% of boron oxide, 8wt% of sodium oxide, and 1wt%-5wt% of copper oxide. %-12wt%, cuprous oxide 5wt%-8wt%, barium oxide 2wt%-3.5wt%, chromium oxide 3wt%-8wt%, nickel oxide 3.5wt%-7wt%, tin oxide 1.5wt%-2.5wt%, silicon carbide 2wt%-5wt%; more preferably, silicon dioxide 50wt%-55wt%, boron oxide 10wt%-12wt%, sodium oxide 10wt%-12wt%, cuprous oxide 5wt%-7wt%, barium oxide 2wt%-3.5wt%, chromium oxide 6wt%-6.5wt%, nickel oxide 4wt%-6wt%, tin oxide 1.5wt%-2wt%, silicon carbide 2wt%-3.5wt%.

[0034] In the present invention, silicon dioxide is the main component of glass and the skeleton of glass. It can increase the viscosity of glass liquid and improve the mechanical strength of glass. The present invention limits the silicon dioxide content to 40wt%-65wt%, which can reduce the melting temperature of glass liquid while meeting the strength of hollow glass microspheres, reduce energy consumption in the preparation process, and reduce production costs; boron oxide can improve the physical and chemical properties of glass, improve the transparency, heat resistance and corrosion resistance of glass, and can also reduce the melting point and viscosity of glass, promote the fluidity and formability of glass. Too low a content will increase the melting temperature of glass liquid and reduce transparency. Too much a content will loosen the glass network structure and increase the thermal expansion coefficient of glass. It will also work together with barium oxide to affect the refractive index effect of hollow glass microspheres; sodium oxide has a low melting point and good melting properties, can greatly reduce the viscosity of glass liquid, is a flux for manufacturing glass, can reduce the melting temperature of glass, accelerate the melting rate The degree of sodium oxide is too high, which will greatly reduce the chemical stability, thermal stability and mechanical strength of the glass, and easily cause the glass to mold and increase the production cost of the glass; cuprous oxide can enhance the hardness and wear resistance of hollow glass microspheres, and also has an anti-corrosion effect. Coating it on metal materials can significantly slow down rust; barium and other metals exist as oxides, and barium oxide can not only reduce the melting temperature of glass, but also has a high refractive index, which can significantly enhance the heat insulation and cooling performance of the coating; tin oxide has good heat insulation performance and hardness, can significantly enhance the heat insulation performance of the coating, and improve the wear resistance and corrosion resistance of the coating; cuprous oxide, barium oxide, chromium oxide, nickel oxide, tin oxide, and silicon carbide are functional components of hollow glass microspheres. Too high or too low a content will significantly reduce the emissivity and refractive index of the hollow glass microspheres. The present invention limits their contents respectively, which can significantly improve the emissivity and refractive index of the hollow glass microspheres and greatly enhance the heat insulation and thermal insulation performance of the coating.

[0035] When doors and windows are closed, heat is mainly transferred to the room through heat conduction and heat radiation. Cuprous oxide, barium oxide, and chromium oxide have high reflectivity, which can reduce the building's absorption of heat. Nickel oxide, tin oxide, and silicon carbide have high emissivity, which can dissipate heat into the outdoor air in the form of infrared radiation, thereby reducing the temperature of the building's outer surface. In addition, cuprous oxide has an antibacterial effect, which can significantly improve the cleanliness of the coating surface and enhance the coating's thermal insulation performance.

[0036] The hollow glass microspheres contain gas, which can not only improve the elasticity of the coating and prevent the coating from cracking and falling off due to thermal expansion and contraction; it can also enhance the waterproof, anti-fouling, and anti-corrosion properties of the coating, and reduce the unit volume cost of the coating; in addition, the spherical surface of the hollow glass microspheres has a reflective effect on light, and the air contained in the tightly arranged hollow glass microspheres can reduce the thermal conductivity of the coating, further improving the thermal insulation performance of the coating.

[0037] In the present invention, boron oxide and barium oxide work together to affect the refractive index effect of the product; cuprous oxide, chromium oxide, nickel oxide and silicon carbide work together to affect the emissivity effect of hollow glass microspheres. In the present invention, both emissivity and refractive index are required, and the two have an impact on each other. The composition and content of each element need to cooperate with each other, and each performance can meet the requirements of the present invention.

[0038] In an optional embodiment, the particle size of the hollow glass microspheres is 10 μm-50 μm.

[0039] In a second aspect, the present invention also provides a method for preparing hollow glass microspheres, comprising the following steps:

[0040] (1) weighing quartz sand, boric acid, soda ash, cuprous oxide, barium sulfate, chromium oxide, nickel oxide, tin oxide, silicon carbide, and a foaming agent, mixing them, and heating them once at 1100° C. to 1250° C. for 20 min to 60 min to obtain molten glass; rapidly cooling the molten glass, and grinding it to obtain a glass powder containing gas;

[0041] (2) reheating the glass powder at 400° C.-800° C. for 10 min-30 min to obtain;

[0042] The mass ratio of the quartz sand, the boric acid, the soda ash, the cuprous oxide, the barium sulfate, the chromium oxide, the nickel oxide, the tin oxide, the silicon carbide and the foaming agent is 40-65:8.88-26.64:8.55-25.65:2-8:1.52-7.61:2-10:3.5-7.5:1.5-3:1-5:4-8; the foaming agent includes at least one of carbon powder, carbonate, sulfate, nitrate and manganese dioxide; the carbonate includes at least one of sodium carbonate, calcium carbonate and magnesium carbonate; the sulfate includes at least one of sodium sulfate and calcium sulfate; the nitrate includes at least one of lithium nitrate, sodium nitrate and potassium nitrate.

[0043] In the third aspect, the present invention also provides a thermal insulation coating, including the above-mentioned hollow glass microspheres and water-based coating, the mass of the hollow glass microspheres accounts for 5wt%-40wt% of the thermal insulation coating; the water-based coating includes at least one of water-based polyurethane, water-based polyacrylic resin, and water-based silicone acrylic coating.

[0044] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.

[0045] Example 1

[0046] This embodiment provides a method for preparing hollow glass microspheres, comprising the following steps:

[0047] (1) 55 mg of quartz sand, 19.54 mg of boric acid, 17.10 mg of soda ash, 6 mg of cuprous oxide, 4.57 mg of barium sulfate, 6 mg of chromium oxide, 5 mg of nickel oxide, 2 mg of tin oxide, 2 mg of silicon carbide and 5.5 mg of carbon powder were weighed and mixed, and heated at 1175° C. for 40 min to obtain molten glass liquid, which was rapidly cooled into granular glass and then ground to obtain glass powder containing gas inside;

[0048] (2) The glass powder is sintered in a high-temperature furnace at 600° C. for 0.3 h, and the gas in the powder further expands to form hollow glass microspheres with a particle size of 10-50 μm; wherein, in terms of weight percentage, the hollow glass microspheres include 55 wt% silicon dioxide, 11 wt% boron oxide, 10 wt% sodium oxide, 6 wt% cuprous oxide, 3 wt% barium oxide, 6 wt% chromium oxide, 5 wt% nickel oxide, 2 wt% tin oxide and 2 wt% silicon carbide; wherein the refractive index of cuprous oxide is 2.7, the refractive index of chromium oxide is 2.5, the refractive index of barium oxide is 1.64, the emissivity of chromium oxide is 0.83, the emissivity of nickel oxide is 0.9, and the emissivity of silicon carbide is 0.9.

[0049] Example 2

[0050] This embodiment provides a method for preparing hollow glass microspheres, comprising the following steps:

[0051] (1) 55 mg of quartz sand, 19.54 mg of boric acid, 17.10 mg of soda ash, 6 mg of cuprous oxide, 4.57 mg of barium sulfate, 6 mg of chromium oxide, 5 mg of nickel oxide, 2 mg of tin oxide, 2 mg of silicon carbide and 5.5 mg of carbon powder were weighed and mixed, and heated at 1100° C. for 60 min to obtain molten glass liquid, which was rapidly cooled into granular glass and then ground to obtain glass powder containing gas inside;

[0052] (2) The glass powder is sintered in a high-temperature furnace at 800° C. for 0.3 h, and the gas in the powder further expands to form hollow glass microspheres with a particle size of 10-50 μm; wherein, in terms of weight percentage, the hollow glass microspheres include 55 wt% of silicon dioxide, 11 wt% of boron oxide, 10 wt% of sodium oxide, 6 wt% of cuprous oxide, 3 wt% of barium oxide, 6 wt% of chromium oxide, 5 wt% of nickel oxide, 2 wt% of tin oxide and 2 wt% of silicon carbide; wherein the refractive index of cuprous oxide is 2.7, the refractive index of chromium oxide is 2.5, the refractive index of barium oxide is 1.64, the emissivity of chromium oxide is 0.83, the emissivity of nickel oxide is 0.9, and the emissivity of silicon carbide is 0.9.

[0053] Example 3

[0054] This embodiment provides a method for preparing hollow glass microspheres, comprising the following steps:

[0055] (1) 55 mg of quartz sand, 19.54 mg of boric acid, 17.10 mg of soda ash, 7 mg of cuprous oxide, 5.33 mg of barium sulfate, 6.5 mg of chromium oxide, 4 mg of nickel oxide, 1.5 mg of tin oxide, 1.5 mg of silicon carbide and 5.5 mg of calcium sulfate were weighed and mixed, and heated at 1250° C. for 20 min to obtain molten glass liquid, which was rapidly cooled into granular glass and then ground to obtain glass powder containing gas inside;

[0056] (2) The glass powder is sintered in a high-temperature furnace at 400° C. for 0.5 h, and the gas in the powder further expands to form hollow glass microspheres with a particle size of 10-50 μm; wherein, in terms of weight percentage, the hollow glass microspheres include 55 wt% silicon dioxide, 11 wt% boron oxide, 10 wt% sodium oxide, 7 wt% cuprous oxide, 3.5 wt% barium oxide, 6.5 wt% chromium oxide, 4 wt% nickel oxide, 1.5 wt% tin oxide and 1.5 wt% silicon carbide; wherein the refractive index of cuprous oxide is 2.7, the refractive index of chromium oxide is 2.5, the refractive index of barium oxide is 1.64, the emissivity of chromium oxide is 0.83, the emissivity of nickel oxide is 0.9, and the emissivity of silicon carbide is 0.9.

[0057] Example 4

[0058] This embodiment provides a method for preparing hollow glass microspheres, comprising the following steps:

[0059] (1) Weighing 50 mg of quartz sand, 21.31 mg of boric acid, 23.94 mg of soda ash, 6 mg of cuprous oxide, 4.57 mg of barium sulfate, 6 mg of chromium oxide, 5 mg of nickel oxide, 2 mg of tin oxide, 2 mg of silicon carbide and 5.5 mg of calcium sulfate, mixing them, heating them at 1150° C. for 40 min to obtain molten glass, rapidly cooling them into granular glass and grinding them to obtain glass powder containing gas inside;

[0060] (2) The glass powder is sintered in a high-temperature furnace at 500° C. for 0.3 h, and the gas in the powder further expands to form hollow glass microspheres with a particle size of 10-50 μm; wherein, in terms of weight percentage, the hollow glass microspheres include 50 wt% silicon dioxide, 12 wt% boron oxide, 14 wt% sodium oxide, 6 wt% cuprous oxide, 3 wt% barium oxide, 6 wt% chromium oxide, 5 wt% nickel oxide, 2 wt% tin oxide and 2 wt% silicon carbide; wherein the refractive index of cuprous oxide is 2.7, the refractive index of chromium oxide is 2.5, the refractive index of barium oxide is 1.64, the emissivity of chromium oxide is 0.83, the emissivity of nickel oxide is 0.9, and the emissivity of silicon carbide is 0.9.

[0061] Example 5

[0062] This embodiment provides a method for preparing hollow glass microspheres, comprising the following steps:

[0063] (1) Weighing 55 mg of quartz sand, 19.54 mg of boric acid, 17.10 mg of soda ash, 5 mg of cuprous oxide, 3.04 mg of barium sulfate, 5.5 mg of chromium oxide, 6 mg of nickel oxide, 2.5 mg of tin oxide, 3 mg of silicon carbide and 7 mg of calcium sulfate, mixing them, heating them at 1200° C. for 30 min to obtain molten glass, rapidly cooling them into granular glass and then grinding them to obtain glass powder containing gas inside;

[0064] (2) The glass powder is sintered in a high-temperature furnace at 700° C. for 0.4 h, and the gas in the powder further expands to form hollow glass microspheres with a particle size of 10-50 μm; wherein, in terms of weight percentage, the hollow glass microspheres include 55 wt% silicon dioxide, 11 wt% boron oxide, 10 wt% sodium oxide, 5 wt% cuprous oxide, 2 wt% barium oxide, 5.5 wt% chromium oxide, 6 wt% nickel oxide, 2.5 wt% tin oxide and 3 wt% silicon carbide; wherein the refractive index of cuprous oxide is 2.7, the refractive index of chromium oxide is 2.5, the refractive index of barium oxide is 1.64, the emissivity of chromium oxide is 0.83, the emissivity of nickel oxide is 0.9, and the emissivity of silicon carbide is 0.9.

[0065] Example 6

[0066] This embodiment provides a method for preparing hollow glass microspheres, comprising the following steps:

[0067] (1) 55 mg of quartz sand, 19.54 mg of boric acid, 17.10 mg of soda ash, 6 mg of cuprous oxide, 4.57 mg of barium sulfate, 6 mg of chromium oxide, 5 mg of nickel oxide, 2 mg of tin oxide, 2 mg of silicon carbide and 7.5 mg of calcium carbonate were weighed and mixed, and heated at 1250° C. for 50 min to obtain molten glass liquid, which was rapidly cooled into granular glass and then ground to obtain glass powder containing gas inside;

[0068] (2) The glass powder is sintered in a high-temperature furnace at 600° C. for 0.5 h, and the gas in the powder further expands to form hollow glass microspheres with a particle size of 10-50 μm; wherein, in terms of weight percentage, the hollow glass microspheres include 55 wt% of silicon dioxide, 11 wt% of boron oxide, 10 wt% of sodium oxide, 6 wt% of cuprous oxide, 3 wt% of barium oxide, 6 wt% of chromium oxide, 5 wt% of nickel oxide, 2 wt% of tin oxide and 2 wt% of silicon carbide; wherein the refractive index of cuprous oxide is 2.7, the refractive index of chromium oxide is 2.5, the refractive index of barium oxide is 1.64, the emissivity of chromium oxide is 0.83, the emissivity of nickel oxide is 0.9, and the emissivity of silicon carbide is 0.9.

[0069] Example 7

[0070] This embodiment provides a method for preparing hollow glass microspheres, comprising the following steps:

[0071] (1) Weighing 45 mg of quartz sand, 17.76 mg of boric acid, 20.52 mg of soda ash, 8 mg of cuprous oxide, 7.61 mg of barium sulfate, 10 mg of chromium oxide, 7.5 mg of nickel oxide, 1.5 mg of tin oxide, 1 mg of silicon carbide and 5.5 mg of carbon powder, mixing them, heating them at 1175° C. for 40 min to obtain molten glass, rapidly cooling them into granular glass and grinding them to obtain glass powder containing gas inside;

[0072] (2) The glass powder is sintered in a high-temperature furnace at 650° C. for 0.17 h, and the gas in the powder further expands to form hollow glass microspheres with a particle size of 10-50 μm; wherein, in terms of weight percentage, the hollow glass microspheres include 45 wt% silicon dioxide, 10 wt% boron oxide, 12 wt% sodium oxide, 8 wt% cuprous oxide, 5 wt% barium oxide, 10 wt% chromium oxide, 7.5 wt% nickel oxide, 1.5 wt% tin oxide and 1 wt% silicon carbide; wherein the refractive index of cuprous oxide is 2.7, the refractive index of chromium oxide is 2.5, the refractive index of barium oxide is 1.64, the emissivity of chromium oxide is 0.83, the emissivity of nickel oxide is 0.9, and the emissivity of silicon carbide is 0.9.

[0073] Example 8

[0074] This embodiment provides a method for preparing hollow glass microspheres, comprising the following steps:

[0075] (1) 60 mg of quartz sand, 26.64 mg of boric acid, 13.68 mg of soda ash, 2 mg of cuprous oxide, 1.52 mg of barium sulfate, 2 mg of chromium oxide, 3.5 mg of nickel oxide, 3 mg of tin oxide, 5.5 mg of silicon carbide and 7.5 mg of carbon powder were weighed and mixed, and heated at 1175° C. for 40 min to obtain molten glass liquid, which was rapidly cooled into granular glass and then ground to obtain glass powder containing gas inside;

[0076] (2) The glass powder is sintered in a high-temperature furnace at 450° C. for 0.4 h, and the gas in the powder further expands to form hollow glass microspheres with a particle size of 10-50 μm; wherein, in terms of weight percentage, the hollow glass microspheres include 60 wt% of silicon dioxide, 15 wt% of boron oxide, 8 wt% of sodium oxide, 2 wt% of cuprous oxide, 1 wt% of barium oxide, 2 wt% of chromium oxide, 3.5 wt% of nickel oxide, 3 wt% of tin oxide and 5.5 wt% of silicon carbide; wherein the refractive index of cuprous oxide is 2.7, the refractive index of chromium oxide is 2.5, the refractive index of barium oxide is 1.64, the emissivity of chromium oxide is 0.83, the emissivity of nickel oxide is 0.9, and the emissivity of silicon carbide is 0.9.

[0077] Example 9

[0078] This embodiment provides a method for preparing hollow glass microspheres, comprising the following steps:

[0079] (1) 65 mg of quartz sand, 8.88 mg of boric acid, 8.55 mg of soda ash, 4 mg of cuprous oxide, 6.09 mg of barium sulfate, 3 mg of chromium oxide, 7 mg of nickel oxide, 3 mg of tin oxide, 4 mg of silicon carbide and 7.5 mg of lithium nitrate were weighed and mixed, and heated at 1175° C. for 40 min to obtain molten glass liquid, which was rapidly cooled into granular glass and then ground to obtain glass powder containing gas inside;

[0080] (2) The glass powder is sintered in a high-temperature furnace at 600° C. for 0.5 h, and the gas in the powder further expands to form hollow glass microspheres with a particle size of 10-50 μm; wherein, in terms of weight percentage, the hollow glass microspheres include 65 wt% of silicon dioxide, 5 wt% of boron oxide, 5 wt% of sodium oxide, 4 wt% of cuprous oxide, 4 wt% of barium oxide, 3 wt% of chromium oxide, 7 wt% of nickel oxide, 3 wt% of tin oxide and 4 wt% of silicon carbide; wherein the refractive index of cuprous oxide is 2.7, the refractive index of chromium oxide is 2.5, the refractive index of barium oxide is 1.64, the emissivity of chromium oxide is 0.83, the emissivity of nickel oxide is 0.9, and the emissivity of silicon carbide is 0.9.

[0081] Comparative Example 1

[0082] This comparative example provides a method for preparing hollow glass microspheres, which is basically the same as the steps of Example 1, except that boric acid is replaced by barium sulfate.

[0083] Comparative Example 2

[0084] This comparative example provides a method for preparing hollow glass microspheres, which is substantially the same as the steps of Example 1, except that chromium oxide is replaced by cuprous oxide.

[0085] Comparative Example 3

[0086] This comparative example provides a method for preparing hollow glass microspheres, which is substantially the same as the steps of Example 1, except that nickel oxide is replaced by cuprous oxide.

[0087] Comparative Example 4

[0088] This comparative example provides a method for preparing hollow glass microspheres, which is substantially the same as the steps of Example 1, except that cuprous oxide is replaced by cupric oxide.

[0089] Comparative Example 5

[0090] This comparative example provides a method for preparing hollow glass microspheres, which is basically the same as the steps of Example 1, except that the mass of quartz sand is 53g, the mass of tin oxide is 4g, and the content of silicon dioxide in the hollow glass microspheres is 53wt%, and the content of tin oxide is 4wt%.

[0091] Comparative Example 6

[0092] This comparative example provides a method for preparing hollow glass microspheres, which is basically the same as the steps of Example 1, except that the mass of quartz sand is 51 g, the mass of silicon carbide is 6 g, and the content of silicon dioxide in the hollow glass microspheres is 51 wt %, and the content of silicon carbide is 6 wt %.

[0093] Experimental Example 1

[0094] The hollow glass microspheres prepared in the above-mentioned Examples 1 to 9 and Comparative Examples 1 to 6 were subjected to mechanical strength tests according to JC / T2284-2014 "Determination of Isostatic Strength (Hydraulic Pressure Method), Oil Absorption Rate and Floating Rate of Hollow Glass Microspheres";

[0095] Heat resistance test: The hollow glass microspheres prepared in the above Examples 1 to 9 and Comparative Examples 1 to 6 were placed in a quartz crucible, placed in a high-temperature furnace and heated for 10 minutes, taken out to check whether the hollow glass microspheres were damaged, and the damage temperature of the hollow glass microspheres was recorded. The results are shown in the table below.

[0096] Table 1 Performance test results of hollow glass microspheres prepared in various embodiments and comparative examples

[0097]

[0098]

[0099] As can be seen from the above table, the hollow glass microspheres prepared in Examples 1 to 9 have high mechanical strength and good heat resistance; the heat resistance of the hollow glass microspheres prepared in Comparative Example 1 is significantly reduced, because boron oxide can improve the transparency, heat resistance and corrosion resistance of the glass; the heat resistance of the hollow glass microspheres prepared in Comparative Example 2 is significantly reduced, because chromium oxide has high temperature stability and can improve the chemical stability and heat resistance of the glass; the mechanical strength and heat resistance of the hollow glass microspheres prepared in Comparative Example 3 are significantly reduced, because in the glass structure, the high bond strength between nickel and oxygen can significantly enhance the mechanical strength of the glass, and nickel oxide has good stability and can enhance the heat resistance of the glass; the mechanical strength and heat resistance of the hollow glass microspheres prepared in Comparative Example 4 are significantly reduced, because copper oxide has a monoclinic crystal structure, while cuprous oxide has a cubic crystal structure, which can form a more stable structure with the [SiO4] tetrahedral structure of the glass skeleton, which can enhance the strength and thermal stability of the glass; the mechanical strength and heat resistance of the hollow glass microspheres prepared in Comparative Example 5 are significantly reduced, because Sn 4+ The radius is much larger than Si 4+ Too high a tin oxide content will destroy the network structure of the glass, resulting in a decrease in its mechanical strength and heat resistance; the mechanical strength of the hollow glass microspheres prepared in Comparative Example 6 is significantly reduced. This is because silicon carbide has high brittleness and too high a content will reduce the mechanical strength of the glass.

[0100] Experimental Example 2

[0101] The hollow glass microspheres prepared in the above-mentioned Examples 1 to 9 and Comparative Examples 1 to 6 were added to the waterborne polyurethane coating at 20 wt % and mixed evenly. The thermal conductivity was tested according to GB / T 10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials-Heat Flow Meter Method", the reflectivity was tested according to GB / T 25261-2018 "Reflective Insulating Coatings for Buildings", the emissivity was tested according to GJB 8700-2015 "Infrared Emissivity Measurement Method", the waterproof performance was tested according to GB / T 19250-2013 "Polyurethane Waterproof Coating", the antibacterial rate (antifouling performance) was tested according to GB / T 21866-2008 "Determination of Antibacterial Property and Antibacterial Effect of Antibacterial Coatings (Paint Films)", and the anticorrosion performance was tested according to GB / T 1771-2007 "Determination of Neutral Salt Spray Resistance of Paints and Varnishes", and the results are shown in the following table.

[0102] Table 2 Test results of coating properties prepared in various embodiments and comparative examples

[0103]

[0104]

[0105] As can be seen from the above table, the coatings prepared from hollow glass microspheres of Examples 1 to 9 have low thermal conductivity and good thermal insulation and cooling performance, waterproof and anti-fouling and anti-corrosion performance; the thermal conductivity of Comparative Example 1 is significantly increased and the waterproof and anti-fouling and anti-corrosion performance is poor. This is because in the glass structure, boron oxide participates in the formation of the glass grid structure. After omitting the addition of boric acid, the glass structure is not dense enough, so the performance is significantly reduced; Comparative Example 2 has poor thermal insulation and cooling performance. This is because chromium oxide has a higher refractive index and good high-temperature stability. After omitting the addition of chromium oxide, the thermal insulation of the coating will be significantly reduced. The thermal insulation and cooling performance and waterproof performance of comparative example 3 are poor, because nickel oxide has a high emissivity and good stability, and can significantly enhance the mechanical strength and heat resistance of glass. After omitting the addition of nickel oxide, the thermal insulation performance of the coating will be significantly reduced; the antifouling and anticorrosion performance of comparative example 4 are poor, because cuprous oxide has antibacterial and anticorrosive properties, and can kill bacteria on the surface of the coating. Replacing it with cupric oxide will significantly reduce the antifouling and anticorrosion performance of the coating; the thermal conductivity of comparative example 5 is significantly increased, and the waterproof and anticorrosion performance are poor, because Sn 4+ The radius is much larger than Si 4+ Too high a tin oxide content will destroy the network structure of the glass and reduce the thermal insulation, waterproof and corrosion resistance of the coating; the thermal conductivity of Comparative Example 6 is relatively high because silicon carbide has good thermal conductivity, and adding too much will increase the thermal conductivity of the coating.

[0106] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A hollow glass microsphere, characterized in that: The hollow glass microspheres include the following components: 40wt%-65wt% silicon dioxide, 5wt%-15wt% boron oxide, 5wt%-15wt% sodium oxide, 2wt%-8wt% cuprous oxide, 1wt%-5wt% barium oxide, 2wt%-10wt% chromium oxide, 3.5wt%-7.5wt% nickel oxide, 1.5wt%-3wt% tin oxide, and 1wt%-5.5wt% silicon carbide.

2. The hollow glass microsphere according to claim 1, characterized in that: The hollow glass microspheres include the following components: 45wt%-60wt% silicon dioxide, 10wt%-15wt% boron oxide, 8wt%-12wt% sodium oxide, 5wt%-8wt% cuprous oxide, 2wt%-3.5wt% barium oxide, 3wt%-8wt% chromium oxide, 3.5wt%-7wt% nickel oxide, 1.5wt%-2.5wt% tin oxide, and 2wt%-5wt% silicon carbide.

3. The hollow glass microsphere according to claim 2, characterized in that: The hollow glass microspheres include the following components: 50wt%-55wt% of silicon dioxide, 10wt%-12wt% of boron oxide, 10wt%-12wt% of sodium oxide, 5wt%-7wt% of cuprous oxide, 2wt%-3.5wt% of barium oxide, 6wt%-6.5wt% of chromium oxide, 4wt%-6wt% of nickel oxide, 1.5wt%-2wt% of tin oxide, and 2wt%-3.5wt% of silicon carbide.

4. The hollow glass microsphere according to claim 1, characterized in that: The particle size of the hollow glass microspheres is 10 μm-50 μm.

5. A method for preparing hollow glass microspheres, characterized in that: The following steps are involved: (1) weighing quartz sand, boric acid, soda ash, cuprous oxide, barium sulfate, chromium oxide, nickel oxide, tin oxide, and a foaming agent, mixing and heating once to obtain a molten glass liquid; rapidly cooling the molten glass liquid, grinding, and obtaining a glass powder containing gas therein; (2) The glass powder is heated for a second time at 400° C.-800° C. to obtain the obtained product.

6. The method for preparing hollow glass microspheres according to claim 5, characterized in that: The mass ratio of the quartz sand, the boric acid, the soda ash, the cuprous oxide, the barium sulfate, the chromium oxide, the nickel oxide, the tin oxide, the silicon carbide and the foaming agent is 40-65: 8.88-26.64:8.55-25.65:2-8:1.52-7.61:2-10:3.5-7.5:1.5-3:1-5.5:4-8。 7. The method for preparing hollow glass microspheres according to claim 5, characterized in that: The foaming agent includes at least one of carbon powder, carbonate, sulfate, nitrate and manganese dioxide; The carbonate includes at least one of sodium carbonate, calcium carbonate and magnesium carbonate; and / or, The sulfate includes at least one of sodium sulfate and calcium sulfate; and / or, The nitrate comprises at least one of lithium nitrate, sodium nitrate and potassium nitrate; and / or, The primary heating temperature is 1100°C-1250°C, and the heating time is 20min-60min; and / or, The secondary heating time is 10 min-30 min.

8. A heat-insulating coating comprising hollow glass microspheres and water-based coating, characterized in that: The hollow glass microspheres are the hollow glass microspheres described in any one of claims 1 to 4, or the hollow glass microspheres prepared by the preparation method described in any one of claims 5 to 7.

9. The thermal insulation coating according to claim 8, characterized in that: The mass of the hollow glass microspheres accounts for 5wt%-40wt% of the thermal insulation coating; and / or, The water-based paint includes at least one of water-based polyurethane, water-based polyacrylic resin, and water-based silicone-acrylic paint.

10. Use of the thermal insulation coating according to claim 8 or 9 in the field of construction.

Citation Information

Patent Citations

  • Preparation method of high-strength low-density hollow glass bead

    CN101704632A

  • Foaming agent for preparation of hollow glass beads and application of foaming agent

    CN102849947A

  • Glass flake as well as preparation method and application thereof

    CN115650592A

  • Glass microbubbles, raw product, and methods of making the same

    US20160152513A1

Cited By

  • High-performance energy-saving building glass and preparation method thereof

    CN120364954A

  • High-performance energy-saving building glass and preparation method thereof

    CN120364954B

  • Low-melting-point rare earth glass bead, radiation refrigeration coating and preparation method

    CN120622807A

  • Low-melting-point rare-earth glass microspheres, radiation-cooling coatings and their preparation methods

    CN120622807B